Geographic heterogeneity of SARS-CoV-2 circulation in Abidjan, Ivory Coast: a prospective study - Moussa Doumbia; Daouda Sevede; Viviane Kouakou; Pascal Pineau (Journal of Infection in Developing Countries)
Introduction: Few studies on SARS-CoV-2 seroprevalence in Ivory Coast have been conducted since the first case was reported on March 11, 2020. The main objective of this study was to observe and better understand the circulation of SARS-CoV-2 in Abidjan.